KETERLIBATAN DEWAN PERWAKILAN RAKYAT DALAM PENGISIAN JABATAN HAKIM AGUNG DAN HAKIM KONSTITUSI DITINJAU DARI PERSPEKTIF KETATANEGARAAN INDONESIA - H. ISMAIL MZ (Universitas Mahasaraswati K. Mataram, 2022)
The involvement of the DPR in filling positions The Supreme Court and the Constitutional Court have the potential to create a number of new problems in the context of the Indonesian state administration. One example is the increase in the authority of the DPR and is very decisive in the selection and determination process of Supreme Court Justices and Constitutional Justices, where this often leads to excesses, namely the occurrence of politicization, collusion and nepotism. In this research, two problems are formulated as follows: first, how is the power position of the DPR involved in filling the Supreme Court and Constitutional Justices in the Indonesian constitutional system?; Second, has this involvement been in line with the principles and principles of power sharing and checks and balances? The methodology used in this research is a normative research method using secondary data sourced from legal materials, while the approach is carried out using a conceptual approach, a case approach and legislation. From the results of this study, several conclusions can be drawn, among others, first, with the involvement of the DPR in filling the positions of supreme justices and constitutional judges as part of the demands for reform that gave birth to transitional democracy after the fall of the New Order regime. Second, the involvement of the DPR institution is a deviation from the principle of power sharing, and does not reflect the principle of checks and balances, because the legislature plays a very important role in determining state agency officials, starting from the selection process to determining officials, while the role of the President is only to inaugurate and ratify officials who has been approved by the DPR.